Implementasi Kebijakan Alokasi Dana Desa (ADD) Terhadap Peningkatan Pembangunan Desa Pada Kecamatan Merek, Kabupaten Karo, Sumatera Utara - Vina Maria Ompusunggu; Rikawati Ginting Munthe (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2020)
The research was carried out in Merek District, Karo Regency, North Sumatra, with the aim of knowing the implementation of village fund allocation policies towards increasing development in the village. This study usess qualitative data which aims to describe in detail and in depth the implementation of village fund allocation policies for village development. Data collection techniques are carried out by giving respondents several lists of questions in the form of questionnaires and interviews and observations as well as documentation studies in order to obtain complete information. The informants in the study were around 40 people and all of them were used as the total sample. The results of this study found that the implementation of the village fund allocation policy (add) has been implemented in increasing development in the village, such as: pipeline rehabilitation, road widening, maintenance of social and economic service facilities and infrastructure for rural communities, agricultural business training, development of superior village products, namely coffee. arabica, as well as the development of tourist villages.